GEBCO API: A Web-based and RESTful interface for accessing global bathymetric data - Mahmoodi, Kumars; Böling, Jari (Elsevier, 2026)
This paper presents GEBCO API, a web-based and RESTful platform for accessing global bathymetric data from the GEBCO 2024 dataset. The application provides an interactive browser-based interface alongside programmatic API endpoints for retrieving water depth at single locations, batches of points, or user-defined geographic areas. Outputs can be downloaded in NetCDF format, enabling seamless integration into scientific workflows. Developed using FastAPI and HTML and deployed as a cloud-accessible service, the GEBCO API lowers technical barriers to high-resolution bathymetric data, supporting research and engineering applications in oceanography, marine energy, and geospatial analysis.